Israel Feinberg. Fighter for freedom and social justice. With an introd. by D. Dubinsky. [With forew. by J. Breslaw and B. Kaplan. English transl. by L. Steinberg. Italian transl. by G. Valente. Ed. by H. Haskel] (New York, 1948)
English, Italian and Hebrew title and text.